2007
DOI: 10.1103/physrevlett.99.145301
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Dynamics of Superfluid Vortices at Nonzero Temperatures

Abstract: We consider the evolution and dissipation of vortex rings in a condensate at non-zero temperature, in the context of the classical field approximation, based on the defocusing nonlinear Schrödinger equation. The temperature in such a system is fully determined by the total number density and the number density of the condensate. A vortex ring is introduced into a condensate in a state of thermal equilibrium, and interacts with non-condensed particles. These interactions lead to a gradual decrease in the vortex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
61
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 32 publications
7
61
0
Order By: Relevance
“…We have characterized the relaxation of the turbulent condensate with the one-body and two-body decay rates of the vortex number. Our measurement results on the decay rates should provide a quantitative test on finite-temperature theories for vortex dynamics [29][30][31]. One interesting extension of this work would be exploring the crossover regime from 3D to 2D by increasing the axial confinement [17,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have characterized the relaxation of the turbulent condensate with the one-body and two-body decay rates of the vortex number. Our measurement results on the decay rates should provide a quantitative test on finite-temperature theories for vortex dynamics [29][30][31]. One interesting extension of this work would be exploring the crossover regime from 3D to 2D by increasing the axial confinement [17,35].…”
Section: Discussionmentioning
confidence: 99%
“…The local vortex dynamics in a homogeneous system is governed by the temperature T and the chemical potential µ of the system: at finite temperature, a vortex experiences a friction force caused by collisional exchange of atoms between the condensate and the thermal cloud [29][30][31], and the chemical potential determines the vortex core size ξ ∝ µ −1/2 , providing a characteristic length scale in the vortex dynamics. In this subsection, we present the measurement results of the decay rates of the vortex number for various sample conditions.…”
Section: Decay Rate Measurementsmentioning
confidence: 99%
“…The generation, dynamics and decay of simple vortex configurations have been observed and described [1,2,3]. At finite temperatures, the interaction of the condensate with the thermal cloud damps the motion of structures (collective modes, solitons, vortices) [4,5,6]. Current investigations of atomic Bose-Einstein condensates are concerned with this damping [7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The velocity of the curve at the point s is v L = v si − αs × v si , where v si is the self-induced velocity (determined by a Biot-Savart integral over the entire vortex configuration), s ≡ ds /dς is the unit tangent vector at s, and α is a dimensionless temperature dependent friction parameter. In the full expression v L there is a second friction parameter, α , which we have neglected here since it is much smaller than α [23,44,45]. In superfluid helium, outside the phase transition region (less than 1 percent from T c ), α is less than unity and positive [23,44].…”
mentioning
confidence: 99%
“…In the full expression v L there is a second friction parameter, α , which we have neglected here since it is much smaller than α [23,44,45]. In superfluid helium, outside the phase transition region (less than 1 percent from T c ), α is less than unity and positive [23,44]. In atomic condensates, numerical sim-ulations of vortex motion based on the ZNG model have shown that [23] α < 0.03 for T /T c < 0.8.…”
mentioning
confidence: 99%